Grand Canyon [videorecording (DVD)] - Kasdan, Lawrence, 1949-; Kasdan, Lawrence, 1949-; Glover, Danny; Kline, Kevin; Martin, Steve, 1945-; McDonnell, Mary; Parker, Mary-Louise; Woodard, Alfre, 1953- (Twentieth Century Fox Home Entertainment, 2000)
"When a lawyer's car breaks down in a dangerous Los Angeles neighborhood, a tow-truck driver arrives just in time to save his life. The two men begin a deep friendship that sets off a chain of unsettling and surprising events involving their families and friends for years to come."--Container.